Identifying socio-cultural determinants to access : implications for e-governance in the water & sanitation sector - Hill, Wesley Clifton (Department of Information Systems, 2016)
This study identifies socio-cultural determinants to both access to technology, as well as access to water and sanitation services, to build an understanding of how technology use and service delivery interact to either restrict or empower groups to communicate their water and sanitation needs through e-government platforms. Even though South Africa's racist apartheid laws were repealed over two decades ago, water and sanitation services in predominantly black areas of Cape Town are still effected by the structural inequalities rooted in apartheid policies. Frustration over the state of water and sanitation services in these areas frequently erupts into violent and destructive protests. A key piece to reducing these inequalities lies in the city's ability to collect data on the state of water and sanitation infrastructure, and the City of Cape Town has promoted a number of e-Governance initiatives to streamline the process of collecting information from users of water and sanitation services. Among these initiatives is an SMS based fault reporting system, which was envisioned as an inexpensive method for users to easily report service failures to the city. Additionally, the city has adopted other web-based reporting platforms based on popular social media sites and email, which can be accessed using internet enabled mobile phones. However, despite high rates of mobile phone ownership in Cape Town, little is known about how people use them. It is important to know how people use mobile phones in order to gauge whether e-Governance initiatives are accessible to poor and vulnerable populations. This analysis is particularly important for highly stratified societies such as South Africa, since it has been shown that introducing ICT into a service delivery system will not result in social change, but will simply act to amplify the underlying intents and capacities that are already present in the system. The purpose of this study was to identify socio-cultural determinants to water and sanitation access and ICT use, to gauge the capacity of groups with marginal access to water and sanitation services to advocate for improvements using mobile phone enabled fault reporting. The study was carried out as a cross-sectional analysis using chi-square tests to identify correlations between socio-cultural data that was collected during three days of interviews in the township of Imizamo Yethu. A spatial analysis was also employed to visualise geographic patterns of access to water and mobile technology. The results indicate that mobility challenged township residents face barriers to accessing water and sanitation services, and also have limited options for reporting faults using mobile phones. Additional disparities in access to services and mobile phone use were found to be based on geography, economic ability, education, as well as place of birth (foreign born vs. South African born). The results indicate that marginalised segments of the population have very limited capacity to communicate their needs to the municipal government. Therefore it seems that e-Governance in the water and sanitation sector likely perpetuates some of the existing inequalities. Hopefully the information and recommendations brought forward in this study will prove helpful to those working to undo the social fractures caused by decades of exclusionary policies.